Respuesta :
u would multiply everything by the common denominator of 4
-3/4m - 1/2 = 2 + 1/4m....multiply everything by 4 and u get :
-3m - 2 = 8 + m
that will get rid of the fractions....but u could multiply by -4 ...giving u :
3m + 2 = -8 - m
-3/4m - 1/2 = 2 + 1/4m....multiply everything by 4 and u get :
-3m - 2 = 8 + m
that will get rid of the fractions....but u could multiply by -4 ...giving u :
3m + 2 = -8 - m
Answer:
4.
Step-by-step explanation:
We are given that an equation
[tex]\frac{-3}{4}m-\frac{1}{2}=2+\frac{1}{4}m[/tex]
We have to find a number by which each term multiply and eliminate the fractions before solving
We can see that in the given expression
Denominator of first term is 4 and denominator of second term is 2 on left side.
Denominator of second term is 4 on right side
Therefore ,the lcm of 2,4,4
2=[tex]2\times1[/tex]
4=[tex]2\times2\times1[/tex]
LCM of 2 and 4 =[tex]2\times2\times1= 4 [/tex]
Therefore, the number is 4 by which each term is multiplied to eliminate the fractions before solving.
Hence, the answer is 4.